is ko solve kar digiye
Attachments:
![](https://hi-static.z-dn.net/files/dd9/a94ddc9138be7904d10b4ddf4993a263.jpg)
Answers
Answered by
1
Given,
x^2+x=1
x=1-x^2
Now,Putting the value of x in another Equation we get,
((1-x^2)+2)^3+1/((1-x^2)+2)^3
=(1-x^2)^3 +3*(1-x^2)*2 + (2)^3 + 1/ (1-x^2)^3 +3*(1-x^2)*2 + (2)^3
=1+1
=2
x^2+x=1
x=1-x^2
Now,Putting the value of x in another Equation we get,
((1-x^2)+2)^3+1/((1-x^2)+2)^3
=(1-x^2)^3 +3*(1-x^2)*2 + (2)^3 + 1/ (1-x^2)^3 +3*(1-x^2)*2 + (2)^3
=1+1
=2
Similar questions